ANALISIS TEKNIK FOOD PHOTOGRAPHY SEBAGAI MEDIA PROMOSI PADA MASYARAKAT KOTA BATAM - Kevin Antonio; Jimmy Pratama (JURNAL ILMIAH BETRIK, 2022)
Photography is a method of producing images by recording the reflection of light hitting an object. Food photography is widely used by food bloggers and is also commonplace for Instagram application users. Food photography demands that the product photos displayed be more attractive, not just showing the food on the plate, but how to attract the attention of someone who sees it can immediately feel hungry with the appearance of the details and textures presented. Food photography is currently able to be used as an alternative way of developing a business in the business world, one of which is efforts in the development of a business by entrepreneurs or business people. In this study, the author made a photographic design that will be used as culinary marketing to attract the attention of the audience to cause a feeling of wanting to try food objects in the photos displayed. However, producing an interesting photo requires maximum shooting process, supporting light, detailed setup, and the precision of a photographer. In this study, the author used Gregory's formula for 2 media experts in the form of lecturers who are experts in the field of photography or multimedia, 2 content experts in the form of café administrators. In addition, the author also uses google form as a medium to collect test data for respondents of 37 people in Batam City who have seen the results of food photography designs and analyzed using the Likert Scale formula. The test results of 2 media experts and 2 content experts got a coefficient value of "1.00" with a "Very High" level of validity, and the respondent validity test carried out obtained results in the form of an index value of 94% with a qualification level of "Strongly Agree".